Method for improving interface bonding strength of flexible thermoelectric device

By pretreating the surface of flexible thermoelectric materials and magnetron sputtering to deposit metal films, the problem of insufficient interface bonding strength of flexible thermoelectric devices is solved, and flexible thermoelectric devices with high performance and high reliability are achieved.

CN119584839APending Publication Date: 2025-03-07SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410855088.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The traditional interface layer has poor bonding strength in flexible thermoelectric devices, which cannot meet the high performance and high reliability requirements of flexible thermoelectric devices.

Method used

By grinding, ultrasonic cleaning, acid corrosion or sandblasting the surface of flexible thermoelectric materials, the surface roughness is enhanced, and the metal film is deposited as an interface layer using DC magnetron sputtering technology to improve the interface bonding strength between the thermoelectric materials and the metal layer.

Benefits of technology

It significantly improves the interface bonding strength of flexible thermoelectric devices, enhances its output performance and reliability, and is suitable for commercial applications and large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584839A_ABST
    Figure CN119584839A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermoelectric components, and particularly relates to a method for improving the interface bonding strength of a flexible thermoelectric device. In order to solve the key problem of interface connection in the preparation process of the flexible thermoelectric device, the invention provides a method for improving the interface bonding strength of the flexible thermoelectric device, and the method comprises the steps: (1) carrying out the polishing and ultrasonic cleaning of the surface of a flexible thermoelectric material; (2) carrying out acid corrosion or sand blasting treatment, carrying out secondary ultrasonic cleaning, and blow-drying the surface of the flexible thermoelectric material by using compressed nitrogen; and (3) finally, depositing a metal film on the surface of the flexible thermoelectric material by adopting a direct-current magnetron sputtering technology to serve as an interface layer so as to improve the interface bonding strength. The interface bonding strength between the thermoelectric material subjected to surface treatment and the metal film layer is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermoelectric components, and in particular relates to a method for improving the interface bonding strength of a flexible thermoelectric device. Background Art

[0002] Thermoelectric devices usually work in the presence of multiple physical fields, such as temperature field, electric field, force field, etc. During the long-term service of the device, in addition to the stability of the material itself, element diffusion usually occurs between the electrode elements and the thermoelectric material, which seriously reduces the output performance of the device and even destroys the normal use function of the device. Therefore, the physical properties of the interface itself and the bonding state between the thermoelectric material and the electrode will directly affect the output, reliability and service life of the device, which has always been the focus and difficulty of thermoelectric device research.

[0003] The interface layer is generally a single or multi-layer metal connected between the thermoelectric material and the metal electrode. The interface layer and the thermoelectric material should have good bonding strength and small residual stress, and this bonding strength should have a certain temperature resistance and durability to ensure that there will be no sudden breakage and failure as the temperature of the thermoelectric device changes and the use time increases. The interface bonding strength is usually related to a variety of factors, such as the difference in thermal expansion coefficient with the thermoelectric material, the degree of elastic modulus matching, and the difficulty of physical and chemical reactions or diffusion.

[0004] The traditional interface preparation method is to lay the thermoelectric material powder and the interface metal powder in layers in a graphite mold, and then prepare the thermoelectric material / interface structure through spark plasma sintering. However, this traditional interface layer is thick and has poor bonding strength, which is not suitable for flexible thermoelectric devices. Therefore, it is urgent to develop a method to improve the interface bonding strength of flexible thermoelectric devices, so as to promote the application and development of flexible thermoelectric devices. Summary of the invention

[0005] Aiming at the preparation and service requirements of flexible thermoelectric devices, the purpose of the present invention is to provide a method for improving the interface bonding strength of flexible thermoelectric devices. The method provided by the present invention can effectively improve the interface bonding strength between the thermoelectric material and the metal film layer in the flexible thermoelectric device, solve the key problem of interface connection in the preparation process of the flexible thermoelectric device, lay a good foundation for the preparation of high-performance and high-reliability flexible thermoelectric devices, and the method is suitable for commercial application and large-scale production.

[0006] Specifically, the method for improving the interface bonding strength of a flexible thermoelectric device includes: (1) First, the surface of the flexible thermoelectric material is polished and ultrasonically cleaned; (2) After acid etching or sandblasting, the flexible thermoelectric material is then ultrasonically cleaned for a second time, and the surface is dried with compressed nitrogen; (3) Finally, a DC magnetron sputtering technique is used to deposit a metal film on the surface of the flexible thermoelectric material as an interface layer to improve the interface bonding strength.

[0007] Preferably, the flexible thermoelectric material is an Ag2S-based flexible thermoelectric material, and the chemical formula is Ag 2-x Cu x S 1-y M y , wherein x=0-1, y=0-0.5, and M is a solid solution element Se or / and Te; the flexible thermoelectric material is in the shape of a disc with a diameter of 6-10 mm, preferably 10 mm.

[0008] Preferably, in step (1): sandpaper is used for smoothing; the mesh size of the sandpaper is 400 to 1000 meshes; the solvent used for the ultrasonic cleaning is an alcohol solvent, preferably ethanol; the power of the ultrasonic cleaning is 90 to 180 W, and the time is 5 to 10 minutes; the mean square roughness of the surface of the flexible thermoelectric material after ultrasonic cleaning is 20 to 150 nm.

[0009] Preferably, in step (2), the etching solution used for the acid etching is a mixture of nitric acid and hydrofluoric acid, preferably the molar ratio of HNO3, HF and H2O is (1-3):1:(1-6), preferably 3:1:6; the etching time of the acid etching is 2-4 minutes; The parameters of the sandblasting process include: the diameter of the sandblasting particles is 200-400 meshes, the jet pressure is 0.5-1.0 MPa, and the sandblasting time is 5-10 seconds.

[0010] Preferably, in step (2): deionized water, acetone and alcohol are used as solvents respectively for secondary ultrasonic cleaning in sequence; the power of the secondary ultrasonic cleaning is 90 to 180 W; and the cleaning time of each solvent is 5 to 8 minutes.

[0011] Preferably, in step (2): after the surface of the flexible thermoelectric material is dried with compressed nitrogen, the mean square roughness of the surface of the flexible thermoelectric material is 20 to 300 nm.

[0012] Preferably, in step (3): the composition of the metal film is selected from at least one of Mo, Cu, Sn, Au, Ag, and W.

[0013] Preferably, in step (3): the parameters of the DC magnetron sputtering technology include: pre-sputtering gas pressure of 0.9-1.2 Pa, pre-sputtering time of 5-10 minutes, formal sputtering substrate temperature of 30-100°C, sputtering power of 70-300 W, sputtering gas pressure of 0.7-0.9 Pa, and sputtering time of 10-60 minutes.

[0014] Beneficial effects of the present invention: The present invention performs surface pretreatment on the Ag2S-based flexible thermoelectric material to enhance its surface roughness, and uses high vacuum magnetron sputtering technology to deposit metal as an interface layer for connection with the electrode, thereby effectively improving the interface bonding strength between the flexible thermoelectric material and the metal layer, solving the key problem of interface connection in the preparation process of flexible thermoelectric devices, and laying a good foundation for the preparation of high-performance and high-reliability flexible thermoelectric devices. The method is suitable for commercial applications and large-scale production. The interface bonding strength between the thermoelectric material after surface treatment and the metal film layer is significantly improved in the present invention, and the metal film layer does not fall off significantly after the tape is pasted, and the critical load value of the metal film layer is twice that of the untreated sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a scanning electron microscope image of the surface of the Ag2S-based flexible thermoelectric material after sandpaper polishing and sandblasting in Example 1; Figure 2 This is a scanning electron microscope image of the surface of the Ag2S-based flexible thermoelectric material after sandpaper polishing and acid corrosion treatment in Example 2; Figure 3 This is a scanning electron microscope image of the surface of the Ag2S-based flexible thermoelectric material after sandpaper polishing in Comparative Example 1; Figure 4 This is a scanning electron microscope image of the surface of the Ag2S-based flexible thermoelectric material after sandblasting in Comparative Example 3; Figure 5 The mean square roughness test results of the surfaces of the samples of Examples 1-3 and Comparative Examples 1-3 are shown; Figure 6 This is a real picture of Example 1 after magnetron sputtering a metal film on the surface of the Ag2S-based flexible thermoelectric material; Figure 7 This is a real picture of Example 2 after magnetron sputtering a metal film on the surface of the Ag2S-based flexible thermoelectric material; Figure 8 This is a physical picture of comparative example 1 after magnetron sputtering a metal film on the surface of the Ag2S-based flexible thermoelectric material; Fig. 9 The results of the interface bonding strength test of Example 1 by the tape sticking method; Fig.10 The results of the interface bonding strength test by the tape sticking method in Example 2 are as follows; Fig.11 The results of the interface bonding strength test of Comparative Example 1 by the tape sticking method; Fig.12 The results of the critical load test of the film in Example 3 using a micron scratch tester; Fig.13This is the result of the critical load test of the film of Comparative Example 2 using a micron scratch tester. DETAILED DESCRIPTION

[0016] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0017] In the present disclosure, a series of pretreatments are first performed on the surface of the Ag2S-based flexible thermoelectric material to enhance its surface roughness, and then a metal is deposited on the surface using a high vacuum magnetron sputtering technique as an interface layer for connection with the electrode.

[0018] The method provided by the present invention is a series of surface treatments performed on Ag2S-based flexible thermoelectric materials before the deposition of a metal film layer, the main purpose of which is to improve the physical and chemical properties of the surface of the Ag2S-based flexible thermoelectric material, improve the adhesion, uniformity and stability of the film, and provide an ideal substrate for subsequent metal film deposition. Surface treatment plays a vital role in the process before film deposition, directly affecting the structure, quality and interface bonding strength of the final deposited film. The following is an exemplary description of a method for improving the interface bonding strength of a flexible thermoelectric device.

[0019] The surface of the Ag2S-based flexible thermoelectric material is smoothed by sandpaper, and the dust particles visible on the surface are removed by ultrasound (the solvent used can be alcohol, etc.). The Ag2S-based flexible thermoelectric material is characterized in that the material component is Ag 2-x Cu x S 1- y M y , where x = 0 ~ 1, y = 0 ~ 0.5, M is the solid solution element Se, Te. The Ag2S-based flexible thermoelectric material sample is a disc with a diameter of 10 mm.

[0020] This is because the surface of the material after sandpaper polishing has directional scratches, and because the Ag2S-based material is soft in texture, there are Al2O3 and SiO2 embedded particles left over from the sandpaper on the surface of the material after polishing. The particle diameter is about 2 to 8 μm. If it is not cleaned, it will affect the subsequent metal film deposition.

[0021] Acid etching or sandblasting is used, and ultrasonic cleaning is performed with high-purity deionized water, acetone and alcohol in sequence to remove residual sand particles and surface oil to obtain a clean surface, and then the semiconductor surface is blown dry with compressed nitrogen. Among them, the acid etching solution is a mixture of nitric acid and hydrofluoric acid (HNO3:HF:H2O=3:1:6), and the sample is immersed in the acid etching solution for 2 to 4 minutes. The diameter of the sandblasting sand particles is 200 to 400 meshes, the jet pressure is 0.5 to 1.0 MPa, and the sandblasting time is 5 to 10 seconds. The mean square roughness of the sample surface after pretreatment is 20 to 300 nm.

[0022] Preferably, after the sample disc is soaked in acid etching solution or sandblasted, it is ultrasonically cleaned in deionized water, acetone and alcohol in sequence, each time for 5-8 minutes, and then the sample surface is blown dry with compressed nitrogen.

[0023] The purpose of acid corrosion immersion or sandblasting in the present invention is to make the surface of the Ag2S-based flexible thermoelectric material uniformly roughened and enhance the surface roughness, thereby improving the adhesion of the subsequently deposited metal film and the interface bonding strength between the thermoelectric material and the metal film. The present invention uses multiple ultrasonic cleaning after acid corrosion or sandblasting. This is because the Ag2S-based material is soft in texture. After sandblasting, a small amount of sand is embedded on the surface, and the diameter of the sand is about 10 μm. After ultrasonic cleaning with high-purity deionized water, acetone and alcohol in sequence, there is no obvious residual sand and sandpaper embedded particles on the sample surface, and the surface oil can be removed at the same time, providing a clean surface for subsequent metal film deposition.

[0024] The metal film is deposited as the interface layer by direct current magnetron sputtering technology. The pre-sputtering pressure of the magnetron sputtering process is 0.9-1.2 Pa, the pre-sputtering time is 5-10 minutes, the substrate temperature of the formal sputtering is 30-100°C, the sputtering power is 70-300W, the sputtering pressure is 0.7-0.9Pa, and the sputtering time is 10-60 minutes. The metal film layer of magnetron sputtering is selected from Mo, Cu, Sn, Au, Ag, and W.

[0025] The present invention can effectively improve the interface bonding strength between the flexible thermoelectric material and the metal layer, and good interface bonding strength is a necessary condition for preparing high-performance thermoelectric devices. The present invention solves the key problem of interface connection in the preparation process of flexible thermoelectric devices, lays a good foundation for the preparation of high-performance and high-reliability flexible thermoelectric devices, and the method is suitable for commercial applications and large-scale production.

[0026] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0027] Example 1 (1) Place a 10 mm diameter and 2 mm thick Ag2S 0.7 Te 0.3 The surface of the wafer is polished with 400-1000# sandpaper, and ultrasonic cleaning with alcohol is used to remove dust particles visible to the naked eye; (2) sand blasting is performed on the surface of the sample, the diameter of the sand blasting particles is 200-400 mesh, the jet pressure is 0.5-1.0 MPa, and the sand blasting time is 5-10 seconds; (3) The sandblasted sample was ultrasonically cleaned with deionized water, acetone, and alcohol in turn for 5 to 8 minutes each time, and then the sample surface was blown dry with compressed nitrogen; (4) The samples were sent to the sputtering chamber of the high vacuum multi-target magnetron sputtering system, and the background vacuum was pumped to 4×10 - 4 Pa, then argon gas is introduced, and the gas flow rate is automatically adjusted by the computer system according to the sputtering gas pressure; (5) Pre-sputtering is performed first, with a pre-sputtering pressure of 1.1 Pa and a time of 5 minutes, in order to remove impurities and oxide layers on the surface of the metal target; (6) Then, the formal sputtering is carried out, with the substrate temperature being 30 to 100°C, the sputtering power being 70 to 300 W, the sputtering gas pressure being 0.7 to 0.9 Pa, and the sputtering time being 10 to 60 minutes.

[0028] Figure 1 This is a scanning electron microscope image of the sample surface after sandpaper polishing and sandblasting in Example 1. It can be seen from the figure that the surface is uneven and rough in appearance, and there are no obvious residual sand particles and sandpaper embedded particles. Figure 5 The mean square roughness test results of the sample surface show that the mean square roughness of the sample surface is significantly enhanced after sandblasting, and the average roughness is 258.85nm.

[0029] Figure 6 This is a real picture of the metal film after magnetron sputtering of Example 1. From the picture, it can be seen that the surface of the sample is matte white, without obvious metallic luster, and the surface is clean, dry and pollution-free.

[0030] Fig. 9 The results of the interface bonding strength test by the tape pasting method in Example 1 are shown in Figure 1. First, use a utility knife to draw grids on the metal film. The spacing between each grid is equal and all cuts are cut through the surface of the thermoelectric material. Then use tape to paste the grids to ensure that the tape is in good contact with the film. After pasting the tape, slowly tear off the tape immediately, observe the grid morphology where the film falls off, and count. It can be seen from the figure that the metal film is completely and evenly covered on the surface of the thermoelectric material. There is no obvious fall-off after two tape pastings, indicating that the bonding strength between the thermoelectric material surface and the metal film is the highest after sandblasting.

[0031] Example 2 The method for preparing the interface of a flexible thermoelectric device provided in this embodiment 2 refers to that in embodiment 1, except that: in step (2), an acid etching treatment is performed on the surface of the sample, the acid etching solution is a mixture of nitric acid and hydrofluoric acid (HNO3:HF:H2O=3:1:6), and the sample disc is immersed in the acid etching solution for 2 to 4 minutes.

[0032] Figure 5 This is the mean square roughness test result of the sample surface in Example 2. The result shows that the average roughness of the sample surface in Example 2 is 77.66 nm.

[0033] Figure 7 This is a real picture of the metal film after magnetron sputtering of Example 2. It can be seen from the picture that the surface of the sample is gray and has a little reflection.

[0034] Fig.10 The results of the interface bonding strength test by the tape pasting method in Example 2. As can be seen from the figure, after the first tape pasting, the film in a few grids was damaged, and after the second tape pasting, the film in more than half of the grids fell off.

[0035] Example 3 The method for preparing the interface of the flexible thermoelectric device provided in Example 3 is similar to that in Example 1, except that: in step (1), a 10 mm diameter and 2 mm thick Ag2S 0.5 Se 0.5 The surface of the wafer was polished with sandpaper of specifications ranging from 400 to 1000#, and alcohol ultrasound was used to remove dust particles visible to the naked eye on the surface.

[0036] Fig.12 The results of the critical load test of the film by the micron scratch tester in Example 3 are shown in Figure 3. The micron scratch tester moves at a constant speed on the sample surface, while applying a linear load longitudinally. The critical vertical load when the film is damaged can be determined by combining the SEM image and the acoustic signal feedback image, so as to quantitatively characterize the bonding strength of the film. As can be seen from the figure, the critical load of the film of this sample is about 1.1399N, which is twice that of the sample in Example 2, further proving that the sandblasting treatment effectively improves the bonding strength of the interface.

[0037] Comparative Example 1 The method for preparing the interface of a flexible thermoelectric device provided in this comparative example 1 refers to that in Example 1, except that: steps (2) and (3) are omitted, and magnetron sputtering is directly performed after the sample is polished with sandpaper.

[0038] Figure 3This is a scanning electron microscope image of the sample surface after sandpaper polishing of Comparative Example 1. It can be seen from the figure that the sample surface has directional scratches, and because the Ag2S-based material is relatively soft, there are Al2O3 and SiO2 embedded particles left by sandpaper on the material surface after polishing, and the particle diameter is about 2-8μm. Figure 5 This is the mean square roughness test result of the sample surface of Comparative Example 1. The result shows that the average roughness of the sample surface of Comparative Example 1 is 70.05 nm.

[0039] Figure 8 This is a real picture of the metal film after magnetron sputtering of Comparative Example 1. It can be seen from the picture that the surface of the sample is grayish white and has obvious reflection.

[0040] Fig.11 The results of the interface bonding strength test by the tape sticking method for comparative example 1 are shown in the figure. As can be seen from the figure, the film was damaged in half of the grids after the first tape sticking, and almost all of it fell off in the second tape sticking.

[0041] Comparative Example 2 The method for preparing the interface of a flexible thermoelectric device provided in this comparative example 2 refers to that in example 3, except that: steps (2) and (3) are omitted, and magnetron sputtering is directly performed after the sample is polished with sandpaper. Fig.13 The results of the film critical load test using a micron scratch tester for comparative example 2. As can be seen from the figure, the critical load of the film of this sample is about 0.4687N.

[0042] Comparative Example 3 The method for preparing the interface of a flexible thermoelectric device provided in this comparative example 3 refers to that of example 3, except that: step (1) is omitted, sandpaper polishing and alcohol ultrasonic cleaning are not used, and sandblasting is performed directly. Figure 4 This is a scanning electron microscope image of the surface of the Ag2S-based flexible thermoelectric material after sandblasting in comparative example 3. It can be seen from the figure that the sample that has not been sanded and ultrasonically cleaned with alcohol has a small amount of dust and impurity particles embedded on the surface, affecting the cleanliness of the sample surface.

[0043] The surface roughness test of the flexible thermoelectric material after surface pretreatment in Examples 1-2 and Comparative Example 1 shows that: The mean square roughness of the sample surface of Example 1 is 226.66-296.81 nm, with an average value of 258.85 nm; The mean square roughness of the sample surface of Example 2 is 28.20-126.88 nm, with an average value of 77.66 nm; The mean square roughness of the sample surface of Example 3 is 198.40-257.50 nm, with an average value of 232.44 nm; The mean square roughness of the sample surface of Comparative Example 1 is 29.25-129.98 nm, with an average value of 70.05 nm; The mean square roughness of the sample surface in Comparative Example 2 is 23.12-123.56 nm, with an average value of 75.81 nm; The mean square roughness of the sample surface in Comparative Example 3 is 49.45-153.58 nm, with an average value of 100.32 nm.

[0044] It can be seen that the present invention performs a series of pretreatments such as sandpaper polishing, sandblasting, and cleaning on the samples in sequence, so that the surface of the samples is uniformly roughened and the roughness is significantly improved, which is much higher than that of the samples after acid corrosion treatment and the samples only polished with sandpaper.

[0045] The results of the interface bonding strength test of Examples 1-3 and Comparative Examples 1-3 by the tape sticking method show that: The film of the sample in Example 1 was firmly bonded, and there was no obvious detachment after two tape adhesions; In Example 2, the film in a few grids was damaged after the first tape application, and more than half of the grids had the film fall off after the second tape application; The film of the sample in Example 3 was firmly bonded, and there was no obvious detachment after two tape adhesions; In the sample of comparative example 1, the film was damaged in half of the grids after the first tape application, and almost all of it fell off in the second application; The sample of Comparative Example 2 almost completely fell off after the first tape application; In the sample of comparative example 3, the film in 1 / 3 of the grids fell off after the first tape pasting, and the film in more than half of the grids fell off after the second tape pasting.

[0046] It can be seen that the present invention enhances the surface roughness by performing a series of pretreatments such as sandpaper polishing, sandblasting, and cleaning on the sample in sequence, thereby improving the interface bonding strength between the metal film and the thermoelectric material.

[0047] The results of the critical load test of the film of Example 3 and Comparative Example 2 using a micron scratch tester show that: The critical load of the film of the sample of Example 3 is about 1.1399N; The critical load of the film of the sample in Comparative Example 2 is about 0.4687N.

[0048] This further proves that the interface bonding strength of the sample after the surface pretreatment of the present invention is significantly enhanced, which is twice the interface bonding strength of the untreated sample.

[0049] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for improving the interface bonding strength of a flexible thermoelectric device, characterized in that: include: (1) First, the surface of the flexible thermoelectric material is polished and ultrasonically cleaned; (2) After acid etching or sandblasting, the surface of the flexible thermoelectric material is cleaned by ultrasonic cleaning for a second time, and then dried with compressed nitrogen; (3) Finally, a metal film is deposited on the surface of the flexible thermoelectric material using DC magnetron sputtering technology as an interface layer to improve the interface bonding strength.

2. The method for improving the interface bonding strength of a flexible thermoelectric device according to claim 1, characterized in that: The flexible thermoelectric material is an Ag2S-based flexible thermoelectric material, and its chemical formula is Ag 2-x Cu x S 1-y M y , wherein x=0-1, y=0-0.5, and M is a solid solution element Se or / and Te; the flexible thermoelectric material is in the shape of a disc with a diameter of 6-10 mm, preferably 10 mm.

3. The method for improving the interface bonding strength of a flexible thermoelectric device according to claim 1 or 2, characterized in that: In step (1), sandpaper is used for smoothing; the mesh number of the sandpaper is 400 to 1000 meshes; The solvent used for ultrasonic cleaning is an alcohol solvent, preferably ethanol; the power of the ultrasonic cleaning is 90 to 180 W, and the time is 5 to 10 minutes; The mean square roughness of the surface of the flexible thermoelectric material after ultrasonic cleaning is 20 to 150 nm.

4. The method for improving the interface bonding strength of a flexible thermoelectric device according to any one of claims 1 to 3, characterized in that: In step (2), the etching solution used for the acid etching is a mixture of nitric acid and hydrofluoric acid, preferably the molar ratio of HNO3, HF and H2O is (1-3):1:(1-6), preferably 3:1:6; the etching time of the acid etching is 2-4 minutes; The parameters of the sandblasting process include: the diameter of the sandblasting particles is 200-400 meshes, the jet pressure is 0.5-1.0 MPa, and the sandblasting time is 5-10 seconds.

5. The method for improving the interface bonding strength of a flexible thermoelectric device according to any one of claims 1 to 4, characterized in that: In step (2), deionized water, acetone and alcohol are used as solvents for secondary ultrasonic cleaning in sequence; the power of the secondary ultrasonic cleaning is 90 to 180 W; and the cleaning time of each solvent is 5 to 8 minutes.

6. The method for improving the interface bonding strength of a flexible thermoelectric device according to any one of claims 1 to 5, characterized in that: In step (2): after the surface of the flexible thermoelectric material is dried with compressed nitrogen, the mean square roughness of the surface of the flexible thermoelectric material is 20 to 300 nm.

7. The method for improving the interface bonding strength of a flexible thermoelectric device according to any one of claims 1 to 6, characterized in that: In step (3): the composition of the metal film is selected from at least one of Mo, Cu, Sn, Au, Ag, and W.

8. The method for improving the interface bonding strength of a flexible thermoelectric device according to any one of claims 1 to 7, characterized in that: In step (3): the parameters of the DC magnetron sputtering technology include: pre-sputtering gas pressure of 0.9-1.2 Pa, pre-sputtering time of 5-10 minutes, substrate temperature of formal sputtering of 30-100°C, sputtering power of 70-300W, sputtering gas pressure of 0.7-0.9 Pa, and sputtering time of 10-60 minutes.

Citation Information

Patent Citations

  • Preparation method of thin film for micro thermoelectric module

    CN114107927A

  • Preparation method of flexible aluminum electrode film

    CN114540767A

  • Method for metallizing inorganic substrate

    JP1990194163A

  • Sputtering target manufacturing method, sputtering target cleaning method, sputtering target, and sputtering apparatus

    JP2009191323A

  • Pulsed laser direct writing technology-based high-density thermoelectric thick film device design and preparation method

    WO2022237149A1